2021
DOI: 10.1002/marc.202100232
|View full text |Cite
|
Sign up to set email alerts
|

Specific Ion Effects of Azobenzene Salts on Photoresponse of PNIPAm in Aqueous Solutions

Abstract: Ionic species are important to dominate phase separation behaviors of poly(N‐isopropylacrylamide) (PNIPAm) in aqueous solutions. Herein, photoresponsive azobenzene‐based salts with various ions are prepared and their photoresponsive ion effects on clouding temperatures (TcpS) of PNIPAm in aqueous solutions are explored. It is found that, despite of various structures of anions and cations, trans‐TcpS under vis light irradiation are always higher than cis‐TcpS under UV irradiation. Particularly, Hofmeister effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Considering that the only difference was on the chemical structure of cross-linkers, it seemed that the ionic liquid-based cross-linker played an important role to efficiently modulating ion conductivities. We previously reported that, above the LCST, ionic liquids in aqueous solutions would prefer to stay in the PNIPAm aggregation rather than be in the aqueous phase . This was against the general understanding for ionic liquids in water.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Considering that the only difference was on the chemical structure of cross-linkers, it seemed that the ionic liquid-based cross-linker played an important role to efficiently modulating ion conductivities. We previously reported that, above the LCST, ionic liquids in aqueous solutions would prefer to stay in the PNIPAm aggregation rather than be in the aqueous phase . This was against the general understanding for ionic liquids in water.…”
Section: Resultsmentioning
confidence: 93%
“…We previously reported that, above the LCST, ionic liquids in aqueous solutions would prefer to stay in the PNIPAm aggregation rather than be in the aqueous phase. 41 This was against the general understanding for ionic liquids in water. Above the LCST, the ionic liquids having affinity with aggregated PNIPAm would surround the PNIPAm while water, working as a poor solute, would be expelled by PNIPAm.…”
Section: Resultsmentioning
confidence: 99%
“…38,45,[161][162][163] Circumstances where SIEs either deviate from the traditional Hofmeister series or undergo complete reversals (Section 3) are becoming more extensively understood. In particular, it is now known that SIEs can be perturbed by stimuli such as solvent, 43,128 temperature 192,193 and UV radiation, 191 in addition to the more well established changes induced by concentration, 25,172,177 pH, 172,174,176,194 cosolute 33,[178][179][180][181][182][183] and counterion. 44,45,[185][186][187] By contrast, the behaviour of ions at surfaces (Section 4) are still poorly understood, in part due to experimental techniques' inability to delineate the individual effects of cations and anions near the interface.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there has been previous work on light-responsive polymers generally, [188][189][190] only recently 191 have studies investigated UV-activation causes the cation to adopt a cis-conformation and greatly decreases the LCST of pNIPAM (Fig. 11(a)).…”
Section: Stimuli-induced Series Anomaliesmentioning
confidence: 99%
“…Here, we leverage trans – cis isomerization to control ionic conductivity. Past work has reported the modulation of conductivity in solvated small-molecule ionic liquids based on azobenzene due to aggregation mediated by trans – cis isomerization. When incorporated into polymers, the trans – cis isomerization of azobenzene also changes the free volume and thus T g . Moreover, past studies have shown that cis -azobenzene can coordinate with small molecules, including metal cations. We thus hypothesized that light-mediated changes in T g and ion coordination could result in photoswitchable polyelectrolyte conductivity with azobenzene covalently attached to the side chain.…”
Section: Introductionmentioning
confidence: 99%